Perlindungan Hukum Terhadap Penelantaran yang Dilakukan oleh Suami Terhadap Anak dan Istri Pada Putusan Nomor 54/PID/2020/PT MND - Daniel Daniel; Rugun Romaida Hutabarat (UNES Law Review, 2023)
Neglect towards children and spouses is a form of criminal act where an individual, in this case, a husband, neglects his obligations and responsibilities to fulfill the basic rights of his children and wife, resulting in them not receiving adequate care, attention, and protection. The issue in this case arises when a husband has been proven to commit the crime of psychological neglect towards his child, but the Appellate Court instead acquitted the Defendant. This raises the question of how child neglect committed by parents, in this case, a father, is regulated based on child protection laws and laws related to domestic violence, and what considerations influence the Appellate Court to render an acquittal for the Defendant. The main finding of this research is that the responsibility and duty to provide attention and protection to children are not solely the task of a wife but require the joint effort of both the father and mother. One of the considerations that led to the Defendant's acquittal by the Appellate Court is that the Defendant provided a year's worth of child support amounting to Rp 700,000.00, and he has one dependent child whose education was disrupted due to detention by the police. Neglect or emotional neglect of a child can have a negative impact on their self-esteem in building relationships with their peers, as they lose the presence of a father who can serve as a role model and guide in facing the world.